Extramammary Paget Disease of the Vulva: A Case Series Examining Treatment, Recurrence, and Malignant Transformation. Issue 3 (March 2018) - Nitecki, Roni; Davis, Michelle; Watkins, Jaclyn C.; Wu, Yiru E.; Vitonis, Allison F.; Muto, Michael G.; Berkowitz, Ross S.; Horowitz, Neil S.; Feltmate, Colleen M.
Abstract : Objectives: Extramammary Paget disease (EMPD) of the vulva is a rare lesion with a high recurrence rate ranging from 12% to 61%. The rate of underlying adenocarcinoma varies, but in the largest series was reported at 4%. Given the rarity of the disease there is a paucity of data to optimize treatment. This study aims to describe the management and recurrence patterns in a tertiary care setting and to offer suggestions for management in a modern-day setting. Methods: Patients with pathologically confirmed EMPD treated from 2000 to 2015 were retrospectively identified using an IRB approved database. Clinical data were abstracted from the electronic medical record. Pathology underwent central review. Results: Forty-four patients met criteria and underwent central pathology review. Forty-two patients were treated with surgical excision. Alternative treatment modalities included Mohs surgery in 3 patients and medical therapy in 20 patients. The median number of surgical procedures was 1 and the number of procedures ranged from 1 to 16. Twenty-five patients (56.8%) had recurrent disease with a median of 2 (1-6) recurrences per patient. The median disease-free interval was 28.7 months with a median follow up of 45.8 months (1.2-178.9 months). Three patients (7%) had invasive cancer and 7 patients (16%) were diagnosed with a separate malignancy at or following diagnosis of EMPD. Despite radical resection, the majority of patients had positive margins and there was no significant difference in disease recurrence between simple and radical resection ( P = 0.69). Conclusions: Patients with EMPD in this series have a high rate of recurrence. Many undergo multi-modal therapy often with multiple providers. However, patients experience relatively long disease-free intervals with a low rate of associated malignancy. We propose an algorithm for management that focuses on symptom control and minimizing morbidity of treatment intervention once invasive disease has been excluded.